Bedforms: views and new perspectives from the third international workshop on Marine and River Dune Dynamics (MARID3). Issue 3 (3rd January 2013) - Parsons, Daniel R.; Best, Jim
ABSTRACT This Commentary introduces a Special Issue of Earth Surface Processes and Landforms dedicated to the memory of Stephen Coleman (1966–2012) who sadly passed away on July 23, 2012. Stephen was an incredible enthusiast for the study of bedforms and made seminal contributions to our knowledge and understanding of flow, sediment transport and bedform dynamics. Stephen presented a keynote address at MARID 3, which has led to this Special Issue (see Coleman SE, Nikora VI. 2011. Fluvial dunes: initiation, characterization, flow structure. Earth Surface Processes and Landforms36: 39–57. DOI. 10.1002/esp.2096) and was always keen to discuss research, from theory to techniques to experiments. He was always generous with his time and touched many with the influence of his thoughts and intellect. Our community has lost an outstanding scientist and Stephen will be greatly missed by us all. Copyright © 2012 John Wiley & Sons, Ltd.